Multifunctional reaction interfaces for capture and boost conversion of polysulfide in lithium-sulfur batteries. (20th February 2020) - Huang, Cheng; Sun, Tingting; Shu, Hongbo; Chen, Manfang; Liang, Qianqian; Zhou, Ying; Gao, Ping; Xu, Sheng; Yang, Xiukang; Wu, Minli; Jian, Jian; Wang, Xianyou
Abstract: Lithium-sulfur batteries have gotten a growing number of investigations because of its overwhelming superiority in theoretical energy density and cost. Nevertheless, the application process of lithium-sulfur batteries is severely obstructed by disadvantageous shuttle effect, which arises from the dissolution and migration of intermediate polysulfides and its sluggish conversion kinetics. Herein, we design the conductivity-adsorption-catalysis reaction interface, which is constructed by growing NiCo2 S4 nanoparticle on reduced graphene oxide (NiCo2 S4 @rGO), to afford chemical immobilization and conversion promotion of polysulfides. In this structure, rGO with excellent conductivity can ensure rapid electron transfer and well-distributed NiCo2 S4 nanoparticles serve as high-efficiency active sites to anchor polysulfides and accelerate its conversion reaction. Thus, lithium-sulfur batteries with this multifunctional reaction interface deliver improved cycling stability with capacity retention rate of 76% after 500 cycles at 1 C. And a good initial capacity of 776 mAh g −1 is gained under high sulfur loading of 3.6 mg cm −2 . This work supplies promising interface design strategies to enhance polysulfides redox kinetics and alleviate shuttle effect for high-performance lithium-sulfur batteries. Graphical abstract: Image 1 Highlights: A conductivity-adsorption-catalyze reaction interface is demonstrated. The lyophilic property and polar surface is more conducive to the electrolyte infiltration and polysulfide adsorption. NiCo2 S4 @rGO can effectively boost kinetics of polysulfide conversion reaction. Using NiCo2 S4 @rGO in the interlayer exhibits excellent electrochemical performances especially under high sulfur loading.